Strongyloides hyperinfection presenting as proteinlosing enteropathy - Ilavarasi Lakshmanan; Veeraraghavan Krishnamurthy; Prem Kumar; Mohammed Ali (Journal of Digestive Endoscopy, 2017)
Strongyloides stercoralis, a soil-transmitted helminth, affects many people in tropical and subtropical countries. It is known to cause asymptomatic infection in immunocompetent and hyperinfection and disseminated Strongyloides infection in immunocompromised due to autoinfection. Here, we report a case of Strongyloides hyperinfection presenting with proteinlosing enteropathy. The diagnosis was made only with duodenal biopsy as the repeated stool examinations were negative. He was treated with ivermectin and his condition improved.